Prevalence and factors leading to delayed graft function and slow graft function in living donor kidney transplantation at tertiary care hospital, Karachi. - Huma, Anbreen; Saleh, Ambreen (Pakistan Journal of Kidney Diseases, 2024)
Introduction: The level of function of a transplanted kidney in the immediate postoperative period is correlated with long-term graft. Delayed graft function (DGF) is associated with acute rejection, prolonged hospital stays, and healthcare costs, as well as increased rates of graft failure. Objectives of study was to determine the frequency of DGF and Slow graft function (SGF) among living donor kidney transplants. Secondly, to compare frequency of factors responsible for slow and delayed graft function. Subjects and methods: Descriptive study done at Department of Transplantation, from 22nd October 2019 to 23rd April 2020. All patients undergoing first living donor renal transplants of both genders with recipient age 18-50 years and had ESRD due to all causes were included. The data related to donor factors, recipient factors, and transplant factor were noted. The frequency of SGF and DGF was noted after early post-transplant period. The leading factors evaluated for the SGF & DGF were compared with IGF. Results: The mean age of the donors was 32.15 ±8.68 years. Only 9 (5.7%) donors had >50 years age whereas female gender was reported as 65 (41.1%). BMI >30kg/m2 was found in only 2 (1.3%) recipients. The mean warm ischemia time was 1.01 ±1.36. None of the patient had WIT of >30. IGF was found in 154 (97.50%) patients, SGF in 3 (1.9%) and DGF in 1 (0.6%) patient. Conclusion: The frequency of DGF was found to be 0.6% and SGF 1.6% among living donor kidney transplants.